Studi Kualitatif Pengetahuan dan Sikap Mahasiswa Klinik FK Unhas Terhadap Sistem Kepaniteraan Klinik Terkait Standar Kompetensi Dokter - Aristo Aristo; Rosa Dwi Wahyuni (Biology Department, Mathematics and natural science, Tadulako University, 2010)
This research is descriptive research qualitative. Research place are at Wahidin Sudirohusodo teaching hospital and related Hospital of Makassar regional. taking data with the interview and observation Processing with qualitative. Result of research that generally responder have known the general doctor competence standard. Responder attitude to general doctor competence standard, clinical clerkship system, base competence curriculum and competence test still be immeasurable. Knowledge and attitude of FK Unhas clinical students to clinical clerkship system related with general doctor competence standard still be immeasurable because not yet there is socialization officially from head faculty Key words: General doctor competence standard, base competence curriculum.